Vortex formation in unsteady flow over NACA 4412 and NACA 4424 airfoils - Hadi, Muhammad Irfan; Nazri, Mohd.; Abdullah, Aslam (Asian Research Publishing Network (ARPN), 2020)
Over the years, the effects of vortex formation on the aerodynamic performance of airfoils have served as motivation for many research studies. This study takes into account NACA 4412 and NACA 4424 which are cambered airfoils. The simulations performed involve low Reynolds number air flow over the airfoils at several angles of attack. Main attention is given on the separation bubble and vortex shedding phenomena, and the effects of vortex formation on airfoils’ aerodynamic performance as represented by lift and drag coefficients. Apparently, the vortex-influenced velocity curl shows alternating vortex formation along the airfoils’ surfaces and at down streams. Also, the angles of attack influence such formation by developing specific separation bubbles with contrasting fixed points, in particular those along the airfoils’ surfaces.